Peningkatan Keterampilan Menyimak Cerita Anak Melalui Pendekatan Savi (Somatis, Auditori, Visual, Intelektual) Dengan Media Audio Visual Pada Siswa Kelas V Sd Negeri Karangtengah Tahun Ajaran 2015/2016 - PUTRI, ROCHANA MEGA (2016)
The purpose of the research is to determine the increase listening skills children's story by applying the approach SAVI (Somatic, Auditory, Visual, Intellectual) and audio-visual media in class V students of SD Negeri Karangtengah in the academic year 2015/2016. Type of research is the PTK (Classroom Action Research). The subject of study is the fifth grade elementary school teacher Karangtengah and Research Object is a class V students of SD Negeri Karangtengah totaling 12 students. This research conducted in two cycles with each cycle there are two meetings. The results showed an increase in the skill shown as follows: 1) take into account prior to the action 50%, 79.16% the first cycle, second cycle 95.83%, 2) Identifying the topic of the story before action 16.66 %%, the first cycle 49.99 %, second cycle 87.49%, 3) Answering questions before the action of 25%, 62.5% the first cycle, second cycle 87.49%, 4) Retelling the story before action of 50%, 58.33% the first cycle, cycle II 87.49%. Learn to listen to students' test results also increased visits from the study before the actions 41.66%, 66.66% the first cycle, the second cycle of 100% .Kesimpulan this study is to approach application SAVI (Somatic, Auditory, Visual, Intellectual) and media audio-visual equipment can enhance children's story listening skills class V students of SD Negeri Karangtengah. Keywords: listening skills, SAVI approach, audio-visual media.